Role of insulin-like growth factor binding protein-3 in glucose and lipid metabolism - Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2013)
Insulin-like growth factor binding protein (IGFBP)-3 has roles in modulating the effect of IGFs by binding to IGFs and inhibiting cell proliferation in an IGF-independent manner. Although recent studies have been reported that IGFBP-3 has also roles in metabolic regulation, their exact roles in adipose tissue are poorly understood. In this review, we summarized the studies about the biological roles in glucose and lipid metabolism. IGFBP-3 overexpression in transgenic mice suggested that IGFBP-3 results in glucose intolerance, and insulin resistance. IGFBP-3 knockout (KO) mice exhibited normal insulin level and glucose response after glucose challenge. More recent study in IGFBP-3 KO mice with a high-fat diet demonstrated that IGFBP-3 KO mice exhibited elevated fasting glucose and insulin, but normal response to glucose challenge, suggesting that IGFBP-3 KO mice may induce insulin resistance even though preserved insulin sensitivity. In vitro and in vivo studies using 3T3-L1 adipocytes and rat, IGFBP-3 induced insulin resistance by inhibiting glucose uptake. In contrast, the reduced levels of IGFBP-3 in obesity might induce insulin resistance by suppression of IGFBP-3's anti-inflammatory function, suggesting IGFBP-3 has a protective effect on insulin resistance. Also, proteolysis of IGFBP-3 might contribute to the insulin resistance in obesity and type 2 diabetes mellitus. In addition, IGFBP-3 inhibited adipocyte differentiation, suggesting IGFBP-3 may contribute to the insulin insensitivity. Taken together, it is not yet certain that IGFBP-3 has a protective effect or enhancing effect on insulin resistance, and more studies will be needed to clarify the roles of IGFBP-3 in metabolic regulation.